Unlocking Communication Wonders: Exploring Transmitter and Receiver Concepts with p5.js - Septian, Firza (Journal Software, Hardware and Information Technology, 2024)
This research presents comprehensive results in various forms such as images, graphs, tables, etc., to facilitate a profound understanding of the developed transmitter-receiver simulation using p5.js. Each component, including setting the canvas, dynamic display, user interaction, binary conversion, transmitter and receiver objects, simulation reset, and testing and evaluation, is thoroughly discussed in separate subsections. A comparative analysis with previous studies is incorporated for enhanced context. The testing phase not only validates the simulation's functionality and accuracy but also emphasizes its role as a potent educational tool. The successful execution of the experiment attests to the codebase's robustness, confirming its ability to effectively illustrate digital communication fundamentals. The visualization of binary signals enhances the project's educational dimension, transforming intricate concepts into an accessible, interactive learning experience. Future testing and refinements present exciting opportunities to augment user experience and extend simulation capabilities. This positive outcome establishes a solid foundation for the program's educational utility, making it a valuable resource for imparting digital communication knowledge. In conclusion, the validated transmitter-receiver simulation marks a significant milestone, combining functionality, visual representation, and potential enhancements. Positioned as an innovative educational technology, it fosters curiosity and understanding in learners exploring digital communication nuances.